2019
DOI: 10.3390/f10060474
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mixed-Effects Individual-Tree Basal Area Increment Model for Oaks (Quercus spp.) Considering Forest Structural Diversity

Abstract: In the context of uneven-aged mixed-species forest management, an individual-tree basal area increment model considering forest structural diversity was developed for oaks (Quercus spp.) using data collected from 11,860 observations in 845 sample plots from the 7th (2004), 8th (2009), and 9th (2014) Chinese National Forest Inventory in Hunan Province, south-central China. Since the data was longitudinal and had a nested structure, we used a linear mixed-effects approach to construct the model. We also used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 86 publications
(132 reference statements)
3
19
0
Order By: Relevance
“…The use of a linear model is considered in general to give a good approximation of an initial growing phase or for a very slow growth process. Vice versa, "logistic" or "Gompertz" models are expected to fit better for more complex growing behaviours [29,44]. The very large dataset considered in the analysis supports, within the aim of this study, the linear growth model approximation to perform best, allowing us to reduce the model complexity by however achieving a suited prediction accuracy.…”
Section: Comparison Of the Two Growth Rate Modelssupporting
confidence: 57%
“…The use of a linear model is considered in general to give a good approximation of an initial growing phase or for a very slow growth process. Vice versa, "logistic" or "Gompertz" models are expected to fit better for more complex growing behaviours [29,44]. The very large dataset considered in the analysis supports, within the aim of this study, the linear growth model approximation to perform best, allowing us to reduce the model complexity by however achieving a suited prediction accuracy.…”
Section: Comparison Of the Two Growth Rate Modelssupporting
confidence: 57%
“…Comparatively, conditional R 2 values generally appear to be higher than the marginal R 2 values, which indicates a significant improvement in explaining variations in NDVI by introducing both random-effects and fixed-effects variables. This finding is consistent with previous studies showing that mixed effects models fitted data better than fixed effects models in terms of R 2 values [30], [33]. The results obtained for three forest types were then compared by the amount of NDVI variance explained by each random intercept and random meteorology-slope model.…”
Section: Resultssupporting
confidence: 91%
“…Additionally, to deal with spatial variabilities LMM can relax the assumption of independence. For instance, LMM considers spatial dependence and spatial heterogeneity in modeling processes to deal with spatial effects of forests with different spatial patterns of tree locations [28], [31], [32], [33]. Previous studies have demonstrated that the LMM is capable of characterizing the variance parameters of random effects in model residuals, and of obtaining more accurate predictions than those derived from general fixed effects models.…”
Section: Application Of Random Effects To Explore the Gulf Of Mexico mentioning
confidence: 99%
“…Natural oak forests are considered a reservoir of great biological diversity, constituting one of the most important ecosystems in Europe. In Northwestern Spain, the presence of the Quercus tree species in forests is an indicator of ecological maturity [2][3][4][5], as they are responsible for maintaining the physicochemical and microclimatic characteristics of this ecosystem [4]. The study of oak is not only essential to assess the ecological conservation of forests, but it is of great economic importance to timber and livestock industries [2].…”
Section: Introductionmentioning
confidence: 99%